The Impact of Antiviral Resistance on Herpetic Keratitis. Issue 3 (11th March 2023) - Moshirfar, Majid; Kelkar, Neil; Peterson, Telyn; Bradshaw, Justin; Parker, Lawsen; Ronquillo, Yasmyne C.; Hoopes, Phillip C.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Herpes simplex keratitis resistance to antiviral treatment presents a growing concern. The herpes simplex virus has many different mechanisms of resistance to antiviral treatment, which have been well described. Resistance to acyclovir occurs because of mutations in the viral thymidylate kinase and DNA polymerase that decrease this enzyme's affinity for its substrate. This article discusses factors that explain the prevalence of this resistance, the ability for recurrences in immunocompromised populations, current treatments for acyclovir-resistant herpes simplex keratitis, and novel therapies for this growing concern.